The Influence of Nationalism's Attitude and Tax Morals on Taxpayer Compliance through Tax Awareness - Tambun, Sihar; Haryati, Ani (Journal of Accounting, Business and Finance Research, 2022)
The purpose of this study is to examine the direct effect of nationalism and tax morale on tax awareness. The effect of the two independent variables on taxpayer compliance through tax awareness is also tested. A quantitative research method was used, and the data was collected via questionnaires. The sample comprises 180 taxpayers. The sample was tested for validity and reliability, and the hypothesis was tested through the SmartsPLS software application. The results of hypothesis testing prove that there is a significant direct effect of nationalism and tax morale on tax awareness, a significant direct effect of tax awareness on taxpayer compliance, and a significant indirect effect of nationalism and tax morale attitudes on taxpayer compliance. From this research, it can be concluded that the government should increase tax awareness by first improving tax morale, then address the attitude toward nationalism.